2020
DOI: 10.3390/pharmaceutics12111123
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Binding of Dietary Phenolic Compounds to Human Serum Albumin and Food-Drug Interactions

Abstract: The distribution of drugs and dietary phenolic compounds in the systemic circulation de-pends on, among other factors, unspecific/specific reversible binding to plasma proteins such as human serum albumin (HSA). Phenolic substances, present in plant-derived feeds, foods, beverages, herbal medicines, and dietary supplements, are of great interest due to their biological activity. Recently, considerable research has been directed at the formation of phenol–HSA complexes, focusing above all on structure–affinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 98 publications
(255 reference statements)
0
22
0
Order By: Relevance
“…Although OLC was not detected in the plasma, four phase I and four phase II metabolites were identified in the plasma with a C max at 2 h. This study demonstrates for the first time that OLC + OH + CH 3 is the main circulating OLC metabolite in rats after OLC consumption, followed by OLC + H 2 O + glucu. The systemic exposure of these metabolites can reflect tissue exposure [ 58 ]. It is worth noting that most in vitro and in vivo studies or clinical trials determining the effects of OLC have focused on the control and progression of different types of cancer, cardiovascular diseases, neurodegeneration, anti-aging processes and immunoinflammatory diseases, but the biological concentrations of OLC [ 6 , 59 ] and its major circulating metabolites were not considered.…”
Section: Resultsmentioning
confidence: 99%
“…Although OLC was not detected in the plasma, four phase I and four phase II metabolites were identified in the plasma with a C max at 2 h. This study demonstrates for the first time that OLC + OH + CH 3 is the main circulating OLC metabolite in rats after OLC consumption, followed by OLC + H 2 O + glucu. The systemic exposure of these metabolites can reflect tissue exposure [ 58 ]. It is worth noting that most in vitro and in vivo studies or clinical trials determining the effects of OLC have focused on the control and progression of different types of cancer, cardiovascular diseases, neurodegeneration, anti-aging processes and immunoinflammatory diseases, but the biological concentrations of OLC [ 6 , 59 ] and its major circulating metabolites were not considered.…”
Section: Resultsmentioning
confidence: 99%
“…The different classes of polyphenols found in dragon fruits like flavonols, flavones, flavanones, phenolic acids, or tannins [ 6 , 17 ] have been shown to exhibit many human health benefits due to their antioxidant activity and may have significant influence on first pass metabolism [ 31 ]. It was also concluded that evaluation of binding of flavonoids to HSA may be useful for preliminary selection of natural products with the highest anti-proliferative activity [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Plasma is an aqueous solution that contains a great variety of substances, including proteins, glucose, mineral ions, hormones, carbon dioxide, and blood cells [8], some of which may interfere with detection of the target analyte. As PCM may have a higher binding affinity to plasma proteins than the parent compounds [99], proteins and other cellular components such as phospholipids need to be removed prior to analysis to reduce potential matrix effects and ion suppression phenomena [100]. An appropriate sample treatment is therefore a crucial step that influences the reliability and accuracy of the analysis [16].…”
Section: Plasmamentioning
confidence: 99%